Israel : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2001)
The Israeli financial system has been growing strong in the wake of a twin process of disinflation and structural transformation. The Bank of Israel plays a key role in liquidity management and absorbing liquidity shocks. All key financial sector activities, except payment systems, are satisfactorily supervised, though coordination among sectors should be improved. The paper also gives information of the Financial System Stability Assessment (FSSA) for Israel on compliance and consistency with international standards and codes relevant for the financial sector.